2021
DOI: 10.1371/journal.pone.0246866
|View full text |Cite
|
Sign up to set email alerts
|

A three-dimensional finite element analysis on the effects of implant materials and designs on periprosthetic tibial bone resorption

Abstract: Introduction Implant material is a more important factor for periprosthetic tibial bone resorption than implant design after total knee arthroplasty (TKA). The virtual perturbation study was planned to perform using single case of proximal tibia model. We determined whether the implant materials’ stiffness affects the degree of periprosthetic tibial bone resorption, and whether the effect of material change with the same implant design differed according to the proximal tibial plateau areas. Materials and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
(55 reference statements)
0
10
0
Order By: Relevance
“…7 Similarly, variations in implant material and design choice have been shown to affect bone resorption. 8,9 Bone formation and resorption are controlled by osteoblast and osteoclast cell activity, each stimulated by multiple factors including localized strain gradient. [10][11][12] Models within the literature, such as Frost's mechanostat, Wolff's law, and Perren's strain theory explain how this mechanism influences the complex and dynamic distribution of mechanical properties in bone.…”
Section: Introductionmentioning
confidence: 99%
“…7 Similarly, variations in implant material and design choice have been shown to affect bone resorption. 8,9 Bone formation and resorption are controlled by osteoblast and osteoclast cell activity, each stimulated by multiple factors including localized strain gradient. [10][11][12] Models within the literature, such as Frost's mechanostat, Wolff's law, and Perren's strain theory explain how this mechanism influences the complex and dynamic distribution of mechanical properties in bone.…”
Section: Introductionmentioning
confidence: 99%
“…Since body weight is transmitted to the tibia through the tibial component in TKA, differences in implant characteristics can directly impact load distribution. Because cobalt-chromium alloys have a higher modulus of elasticity than Ti6Al4V alloys, stress-shielding occurs more in the surrounding bone, 12,29,30 and the thicker the baseplate the more likely bone loss will occur. 8 The shape of the component can also affect the distribution of load, which is related to the patient's anatomical geometry.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, finite element analysis (FEA) has been used in analyzing mechanical stimuli alterations according to the implant design, material, and surgical methods that affect stress-shielding in total joint replacement, 10,11 especially in TKA. Park et al 12 reported the association of periprosthetic tibial bone resorption with tibial component material, and Zhang et al 13 reported that the material and alignment of tibial component had a significant effect on the stress-shielding of the proximal tibia. In addition, Au et al 14 reported that the contribution of loading condition had an important effect on the stress-shielding near the tibial component.…”
Section: Introductionmentioning
confidence: 99%
“…The models were densely meshed by hypermesh (Altair, USA) with a 0.4‐mm element size using linear tetrahedral elements (Fig S1). A previous study showed that models with element sizes less than 1 mm have less than 3% error in strain 23 . The nodes of the coronoid and condylar regions in all directions were constrained to ensure boundary conditions.…”
Section: Methodsmentioning
confidence: 99%